The influence of customer engagement through social media on the purchase intention - Mohd Ishak, Ahmad Nazmi (2017)
The purpose of this research paper is to determine whether customer engagement in social media platform may influence the purchasing intention of customer by interviewing 12 startups business environment based in Malaysia. The finding demonstrates that there are determinants that support customer engagement that will ultimately lead to influencing purchasing intention via social media marketing. Customer engagement has been discussed, where attitude can be influenced by social media influencing purchase intention. The significance of the study has been discussed at length and research object provided. Literature review that is focusing on the impact of customer engagement on the purchase intention and factors that enable the customers to purchase has been highlighted. Research methodology has been conducted, where data collection method, ethical consideration, reliability and generalizability has been conducted. Data analysis has also been done on content development and metrics, customer engagement and Effect of Consumer Engagement on Purchase Intention. The finding of the study shows that social media marketing entirely depends on the type of the product that a particular segment is concerned with. More so, social media marketing enhance customer engagement since the various strategies used act as a source of mouth that makes the customer to contemplate purchasing various products. Lastly, customer engagement has a positive impact towards the purchasing intention, which increase brand loyalty; hence, increase of sales .Additionally, discussions of the study have been done and lastly, conclusion, recommendation and scope of further studies have been discussed at length.